The relationship of parenting patterns for toddlers recipient of BLT (Direct Cash Assistance) with Nutritional Status in Tanjung Ibus Hinai Kiri Langkat Village - Anistya Tri Noveria (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2022)
The efforts to achieve good nutritional status in children under 5 years of age certainly cannot be separated from the monitoring and supervision of parents, especially mother. Mothers have an important role in childrens’s health in terms of providing food and parenting. The aim of this study was to know the relationship between mother’s parenting style and nutritional status of child at Desa Tanjung Ibus Hinai Kiri Langkat. This study used a cross-sectional design with a sample of 47 mothers who have children aged 12-59 months which taken using a purposive-sampling technique. Analysis of data was carried out using descriptive test and Rank-Spearman correlation test. The results of this study showed that 68,09% toodler are malnourished and 31,91% toddlers have normal nutrition. Parenting style based on mother’s parenting are mostly in less category is 70,21%. There is a significant relationship between maternal parenting ang nutritional status of toddlers with a correlation coefficient value is 0,704 (p=0,000).